Digital technology for facilitating inquiry-based learning during the COVID pandemic for human anatomy course - Neeraj Vedi; Puja Dulloo; Praveen Singh (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Linking anatomy with the clinical approach for creating an inquisitive mind for a millennium via the digital platform is the need of the hour. Traditional lecturing makes students have rote memorization of the human anatomy. The inquiry-based project will allow undergraduate medical students to have a deeper understanding of human anatomy along with team building and interpersonal skill development. This approach of teaching would allow students to link the content taught for human anatomy with its clinical applicability and probably generate inquisitiveness for further exploring the course content. The study aimed to appraise and assess the perception of medical students and faculty about the inquiry-based digitalized project presentation. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted for inquiry-based project presentation where students were divided into 15 groups with 15 inquiries, which were presented as projects on a digital platform under the guidance of the facilitator. The perception of students and faculty for the inquiry-based approach was collected using a validated survey questionnaire. The quantitative data were analyzed by SPSS-version 15, using descriptive statistics, Friedman's rank, and thematic analysis for qualitative data. RESULT: In total, 117 students participated in the pre-test and 129 in the post-test part of the study. Also, 79.1% of students appreciated that the inquiry-based project presentation approach allowed them to link anatomy with different courses; 73.6% agreed that this approach has a positive impact on their attitude toward learning anatomy. Then, 75.2% students appreciated of learning new skills using the digital platform. They agreed to have developed leadership (65.1%) and team-building skills (83.7%) and self-directed learning (SDL) improvement (71.3%). However, some students (9.3%) and faculty (16.7%) had been ostracized for presenting their inquiry-based projects on a digital platform, whereas 65.1% of students appreciated this approach. CONCLUSION: Inquiry-based learning approach would allow students to have a deeper understanding of the subject knowledge and skills for the SDL and learn strategies for the usage of virtual technology for literature search.